2017
DOI: 10.1007/s11295-017-1195-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic diversity of the Turkish national hazelnut collection and selection of a core set

Abstract: European hazelnut (Corylus avellana L.) is an economically and nutritionally important nut crop with wild and cultivated populations found throughout Europe and in parts of Asia. This study examined the molecular genetic diversity and population structure of 402 genotypes including 143 wild individuals, 239 landraces, and 20 cultivars from the Turkish national hazelnut collection using simple sequence repeat (SSR) markers. A total of 30 SSR markers yielded 407 polymorphic fragments. Diversity analysis of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The hazelnut collection evaluated was highly polymorphic for its storage proteins as the percentage of polymorphic loci was 82.9%, showing also considerable diversity (h = 0.291 ± 0.029). In fact, using other molecular markers, several studies have consistently shown a great genetic diversity for this tree nut [ 9 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hazelnut collection evaluated was highly polymorphic for its storage proteins as the percentage of polymorphic loci was 82.9%, showing also considerable diversity (h = 0.291 ± 0.029). In fact, using other molecular markers, several studies have consistently shown a great genetic diversity for this tree nut [ 9 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with minor hazelnut-induced allergic reactions might also consider carefully selecting specific hazelnut varieties for possible consumption. In fact, hazelnut is a wind-pollinated species and it has a self-incompatible mating system that enforces cross-pollination; thus, genetic diversity is expected to be high in naturally occurring plants [ 9 ]. The information on overall gene transcription patterns of hazelnut allergens is still very scarce [ 10 , 11 ] and their correlation with expressed proteins/allergens and its allergenic potential was not described.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, woody perennial varieties often remain genetically indistinct from their uncultivated wild counterparts [84]. Comparative multivariate analysis of genome-wide DNA markers shows that cultivated individuals of apple [105], grape [106,107], and European hazelnut [108] appear undifferentiated from either their progenitors or wild relatives, even following selection. Such genetic similarities suggest ongoing gene flow between cultivated selections and wild germplasm following domestication [106], which occurs very regularly [109].…”
Section: Corylus Avellana Corylus Americanamentioning
confidence: 99%
“…European hazelnut ( Corylus avellana L.) is a diploid (2n = 22), monecious, dichogamous, self-incompatible, perennial, wind-pollinated species belonging to the Betulaceae family, and can be grown in bush form or from a single trunk ( Brown et al, 2016 ; Öztürk et al, 2017b ). European hazelnut is commercially important for its nuts.…”
Section: Introductionmentioning
confidence: 99%
“…Randomly amplified polymorphic DNA (RAPD), intersimple sequence repeat (ISSR), and amplified fragment length polymorphism (AFLP) markers have also been used to characterize the relatedness between Turkish hazelnut varieties ( Kafkas et al, 2009 ; Erdoğan et al, 2010 ). Öztürk et al (2017b) also studied the Turkish national hazelnut collection to identify genetic diversity and population structure, as well as selecting a core set which includes the most diverse accessions. This collection consists of 402 different accessions collected from the Black Sea Region including cultivars, landraces and wild accessions, which were classified using SSR markers ( Öztürk et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%